STUDY OF SUICIDAL CASES BY HANGING IN FARIDABAD REGION (Journal of Forensic Medicine & Toxicology, 2019)
World Health Organization (WHO) has defined suicidal act as the injury with varying degrees of lethal intent and suicide as a suicidal act with fatal outcome. According to Indian union health ministry about 1.2 lakh people commit suicide annually. It imposes a huge socioeconomic burden on the society as it takes tolls among the economically productive age-group. We conducted a retrospective study at Faridabad region to know various factors associated with hanging. Objective of this study was to find age and sex distribution of hanging in Faridabad region. A study was carried out in the department of Forensic Medicine at ESIC Medical College, Faridabad in association with BK Civil Hospital, Faridabad. In the present study there were total 254 cases of hanging. Out of these, 57% were males and 43% were females. Most common age-group was 31-40 years. 48% of males and 44% females were in the age-group of 31-40 years. There was no case in the age-group of 0-10 years. In the age-group of more than 50 years, only 3% males and 6% females were the victims. The most common ligature material was cloth material such as chunni or dupatta and saree and rope. The most common reason was financial problems, family problems, relationship issue and chronic illness.
Keywords: Suicide; hanging; ligature material; Relationship issue; financial problem